ALGORITHMIC AND METHODOLOGICAL ASPECTS OF TRANSFORMFTION OF REGIONAL GRAVITY ANOMALIES (ON THE EXAMPLE OF THE KURIL ISLAND ARC) - Dolgal, A.S.; Rashidov, V.A.; Ryzhov, N.V.; Khokhlova, V.V. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2025)
The technique of transforming gravity anomalies for large areas, which uses geodetic coordinates of field points and takes into account the spherical shape of the Earth, is considered. In order to minimize edge effects, two levels of depths for placing equivalent sources (point masses) are used. The parameters of the sources are determined by sequentially solving systems of linear algebraic equations using Kholetskiy and steepest descent methods. High computation speed is achieved by sparsely specifying the field values outside the study area. Preliminary geological reduction of Bouguer anomalies is carried out using the global structure model CRUST1. When solving the direct problem of gravity exploration, a dense packing of spherical parallelepipeds is used. The resulting field transforms are used for further interpretation by probabilistic-statistical methods in the KOSKAD-3D system. The results of the transformation of the gravitational field in the full Bouguer reduction for the Kuril island arc, adjacent water areas and land parts bounded by the coordinates 40°–54° N, 142°–162° E with a total area of about 2.4 million km2 are presented.